Resin composition, bonding film, laminate with resin composition layer attached, laminate and electromagnetic shielding film

KR103034677B1Active Publication Date: 2026-10-21TOAGOSEI CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
KR1020237017369
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-23
Filing Date
2021-10-14
Publication Date
2026-10-21
Estimated Expiration
2041-10-14

Smart Images

  • Figure 112023056769057-PCT00001
    Figure 112023056769057-PCT00001
  • Figure 112023056769057-PCT00002
    Figure 112023056769057-PCT00002
  • Figure 112023056769057-PCT00003
    Figure 112023056769057-PCT00003
Patent Text Reader

Abstract

A resin composition comprising a polyester polyurethane resin (A) and an epoxy resin (B), wherein the isocyanate component constituting the polyester polyurethane resin (A) comprises an isocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms, and a bonding film, a laminate with a resin composition layer attached, a laminate, or an electromagnetic shielding film using the resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polyester-polyurethane-based resin composition as an effective material for manufacturing printed circuit boards, particularly flexible printed circuit boards or build-up multilayer printed circuit boards, which have high adhesion to polyimide films or metals, have heat resistance and moisture resistance of the cured product, and have excellent liquid stability and processability. Furthermore, the invention relates to an electromagnetic shielding film suitable for use in shielding electronic noise generated from an electrical circuit by adhering the resin composition to a release film, a laminate with a resin composition layer attached to a base film, a laminate having a layer formed by curing the resin composition, and a flexible printed circuit board. Background Technology

[0002] The applications of flexible printed circuit boards are expanding because they enable three-dimensional and high-density mounting even in limited spaces. Furthermore, with the recent miniaturization and lightweighting of electronic devices, related products for flexible printed circuit boards are diversifying, and demand is increasing. These related products include flexible copper-clad laminates formed by bonding copper foil to a polyimide film, flexible printed circuit boards with electronic circuits formed on flexible copper-clad laminates, flexible printed circuit boards with reinforcement plates bonded to flexible printed circuit boards, and multilayer boards formed by stacking and bonding flexible copper-clad laminates or flexible printed circuit boards. For example, when manufacturing flexible copper-clad laminates, an adhesive is generally used to bond the polyimide film and the copper foil.

[0003] As for conventional adhesive compositions or conventional laminates, the methods described in Patent Documents 1 to 3 are known.

[0004] Patent Document 1 describes a halogen-free flame-retardant adhesive composition comprising (A) a solvent-soluble polyamide resin that is solid at 25°C, (B) a phenoxy resin, (C) an epoxy resin that does not contain halogen atoms, and (D) a phosphorus-based flame retardant having a structure represented by the following general formula (1), wherein the epoxy resin (C) is an epoxy resin having three or more epoxy groups in one molecule, the content of the phenoxy resin (B) is 100 to 450 parts by mass per 100 parts by mass of the polyamide resin (A), the content of the epoxy resin (C) is 1 to 60 parts by mass per 100 parts by mass of the total of the polyamide resin (A) and the phenoxy resin (B), and the content of the phosphorus-based flame retardant (D) is 5 to 100 parts by mass per 100 parts by mass of the total of the polyamide resin (A) and the phenoxy resin (B). there is.

[0005] In addition, Patent Document 2 describes a laminate characterized by a curable resin composition having two or more carboxyl groups in the molecule, a number average molecular weight of 5,000 to 100,000, and a molecular weight of 1,500 to 10,000 per carboxyl group, an epoxy resin (b) containing two or more epoxy groups in the molecule, and an epoxy resin curing accelerator (c), wherein the curable resin composition capable of maintaining thermoplasticity for a period of 5 months or more at 5°C is laminated on at least one surface of a polyimide film, a polyester film, or a metal foil, and the curable resin composition of the laminate is cured and laminated on a metal foil (including a metal circuit).

[0006] In addition, Patent Document 3 describes a compound containing a carboxyl group, and an acid value (unit: equivalent / 10 6 g) is 100 or more and 1000 or less, and the number average molecular weight is 5.0×10 3 At least 1.0×10 5A resin composition for an adhesive is described, comprising a polyurethane resin (a) having a glass transition temperature of -10°C or higher and 70°C or lower, an epoxy resin (b) containing nitrogen atoms, and an epoxy resin (c) having a dicyclopentadiene backbone, wherein the mixing ratio of the resin (b) is 0.1% or higher and 20% or lower of the total epoxy resin included in the resin composition. Prior art literature

[0007] Japanese Patent Publication No. 5846290, Japanese Published Patent Application No. 2005-125724, Japanese Published Patent Application No. 2010-84005 The problem to be solved

[0008] The problem that the present invention aims to solve is to provide a resin composition having excellent conductivity even after long-term storage (1,000 hours) of the obtained cured product in a high temperature and high humidity environment (85℃, 85%RH) and after a cold and heat cycle test (e.g., -40℃ / 125℃ for 1,000 cycles).

[0009] Another problem that the present invention aims to solve is to provide a bonding film, a laminate with a resin composition layer attached, a laminate, or an electromagnetic shielding film using the resin composition. means of solving the problem

[0010] The means for solving the above problem include the following aspects.

[0011] <1> A resin composition comprising a polyester polyurethane resin (A) and an epoxy resin (B), wherein the diisocyanate component constituting the polyester polyurethane resin (A) comprises a diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms.

[0012] <2> A resin (C) further containing a carboxyl group or a carboxylic acid anhydride structure <1> Resin composition described in

[0013] <3> Polyester polyurethane resin (A) having a molecular weight of 200 to 8,000 per urethane bond <1> or <2> Resin composition described in

[0014] <4> With respect to the total amount of the polyester polyurethane resin (A), epoxy resin (B), resin (C) having a carboxyl group or carboxylic acid anhydride structure, and imidazole silane compound (D) which may be contained as an optional component in the above resin composition, the content of the polyester polyurethane resin (A) is 10 mass% to 90 mass%, and the content of the resin (C) having a carboxyl group or carboxylic acid anhydride structure is 5 mass% to 70 mass%. <1> inside <3> A resin composition described in any one of the following.

[0015] <5> A further containing inorganic filler (E) <1> inside <4> A resin composition described in any one of the following.

[0016] <6> A further containing organic filler (F) <1> inside <5> A resin composition described in any one of the following.

[0017] <7> The above diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms has a hydrocarbon structure. <1> inside <6> A resin composition described in any one of the following.

[0018] <8> A diol component constituting a polyester polyurethane resin (A) comprises a diol compound having a hydrocarbon group having 5 to 32 carbon atoms. <1> inside <7> A resin composition described in any one of the following.

[0019] <9> The above diol compound having a hydrocarbon group having 5 to 32 carbon atoms contains a diol compound having an alicyclic structure or two or more side chains. <8> Resin composition described in

[0020] <10> A polyester polyurethane resin (A) comprises a polyester polyurethane resin having a polyester structure with a number average molecular weight of 8,000 to 30,000. <1> inside <9> A resin composition described in any one of the following.

[0021] <11> The number average molecular weight of the polyester polyurethane resin (A) is 10,000 to 80,000. <1> inside <10> A resin composition described in any one of the following.

[0022] <12> The acid value of the polyester polyurethane resin (A) is 0.1 mgKOH / g to 20 mgKOH / g <1> inside <11> A resin composition described in any one of the following.

[0023] <13> The glass transition temperature of the polyester polyurethane resin (A) is 30°C to 150°C. <1> inside <12> A resin composition described in any one of the following.

[0024] <14> The content of epoxy resin (B) is 1 to 30 parts by mass per 100 parts by mass of polyester polyurethane resin (A). <1> inside <13> A resin composition described in any one of the following.

[0025] <15> The epoxy resin (B) comprises a bisphenol A type epoxy resin and / or a novolak type epoxy resin. <1> inside <14> A resin composition described in any one of the following.

[0026] <16> The content of the resin (C) having a carboxyl group or carboxylic acid anhydride structure is 1 to 100 parts by mass per 100 parts by mass of polyester polyurethane resin (A). <1> inside <15> A resin composition described in any one of the following.

[0027] <17> A resin (C) having a carboxyl group or carboxylic acid anhydride structure comprises at least a portion of a polyamide resin having an acid value and a resin having an acid-modified polyolefin structure. <1> inside <16> A resin composition described in any one of the following.

[0028] <18> further containing metal filler (G) <1> inside <17> A resin composition described in any one of the following.

[0029] <19> The content of the metal filler (G) is 10 to 350 parts by mass with respect to 100 parts by mass of the total amount of the polyester polyurethane resin (A), epoxy resin (B), resin (C) having a carboxyl group or carboxylic acid anhydride structure, and an imidazole silane compound (D) that may be included as an optional component in the resin composition. <18> Resin composition described in

[0030] <20> The metal filler (G) is a conductive filler. <18> or <19> Resin composition described in

[0031] <21> <1> inside <20> A bonding film comprising a resin composition layer in a B-stage state formed by partially curing a resin composition described in any one of the above, and a release film in contact with at least one side of the resin composition layer.

[0032] <22> <1> inside <20> A resin composition layer comprising a resin composition layer formed by any one of the resin compositions, a resin composition layer in a B-stage state formed by partially curing the resin composition, or a cured layer formed by curing the resin composition, and a substrate film in contact with at least one side of the resin composition layer, the resin composition layer in the B-stage state, or the cured layer.

[0033] <23> <1> inside <20> A laminate having a cured layer formed by curing a resin composition described in any one of the above.

[0034] <24> Copper foil, <1> inside <20> A flexible copper-clad laminate having a cured layer formed by curing a resin composition described in any one of the above, and a substrate.

[0035] <25> Copper wiring and, <1> inside <20> A flexible flat cable having a cured layer formed by curing a resin composition described in any one of the above, and a covering material.

[0036] <26> <1> inside <20> An electromagnetic shielding film having a resin composition layer formed by a resin composition described in any one of the above, a resin composition layer in a B-stage state formed by partially curing the resin composition, or a cured layer formed by curing the resin composition. Effects of the invention

[0037] According to the present invention, a resin composition having excellent conductivity can be provided even after long-term storage (1,000 hours) in a high temperature and high humidity environment (85℃, 85%RH) and after a cold and heat cycle test (e.g., -40℃ / 125℃ for 1,000 cycles).

[0038] In addition, according to the present invention, a bonding film, a laminate with a resin composition layer attached, a laminate, or an electromagnetic shielding film using the resin composition can be provided. Specific details for implementing the invention

[0039] The description of the constituent elements described below may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. Furthermore, in this specification, the term "to" is used to mean including the numerical values ​​described before and after it as lower and upper limits.

[0040] In numerical ranges described stepwise in this specification, an upper or lower limit value described in one numerical range may be substituted with an upper or lower limit value of another numerical range described stepwise. Additionally, in numerical ranges described in this specification, an upper or lower limit value of said numerical range may be substituted with a value shown in the examples.

[0041] In the present invention, the amount of each component in the composition refers to the total amount of said plurality of substances present in the composition, unless specifically stated otherwise, in cases where there are multiple substances corresponding to each component in the composition.

[0042] In this invention, the term "process" includes not only independent processes but also cases where the intended purpose of the process is achieved, even if it cannot be clearly distinguished from other processes.

[0043] In the present invention, "mass%" and "weight%" have the same meaning, and "mass part" and "weight part" have the same meaning.

[0044] In addition, in the present invention, a combination of two or more preferred suns is a more preferred sun.

[0045] Additionally, in this specification, "(meth)acrylic" refers to both acrylic and methacrylic or either one.

[0046] In addition, in some of the compounds in this specification, the hydrocarbon chain may be described by a simplified structural formula in which the symbols for carbon (C) and hydrogen (H) are omitted.

[0047] The contents of the present invention will be described in detail below.

[0048] (Resin composition)

[0049] The resin composition of the present invention contains a polyester polyurethane resin (A) and an epoxy resin (B), and the diisocyanate component constituting the polyester polyurethane resin (A) comprises a diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms.

[0050] The resin composition of the present invention can be preferably used as an adhesive composition, more preferably as an adhesive composition for bonding polyimide or metal, and particularly preferably as an adhesive composition for bonding polyimide and metal.

[0051] The inventors have discovered that conventional resin compositions do not have sufficient conductivity when the resulting cured product is subjected to high temperature and high humidity environments and cold / heat cycle tests.

[0052] As a result of careful examination by the inventors, it was discovered that a resin composition containing two types of resins, a polyester polyurethane resin (A) and an epoxy resin (B), wherein the diisocyanate component constituting the polyester polyurethane resin (A) includes a diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms, although the detailed mechanism is unclear, these two types of resins act in harmony with each other and complement each other, and furthermore, because the isocyanate component constituting the polyester polyurethane resin (A) includes a diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms, the hydrophobicity of the resin is improved and the moisture resistance is improved, so the resulting cured product has excellent conductivity even under high temperature and high humidity, and furthermore, due to the stress relief effect by the resin components of the polyester polyurethane resin (A) and the epoxy resin (B), it is possible to provide a resin composition with excellent conductivity even after a cold and hot cycle test.

[0053] In addition, the resin composition of the present invention contains two types of resins, a polyester polyurethane resin (A) and an epoxy resin (B), wherein the molecular weight per urethane bond in the polyester polyurethane resin (A) is 200 to 8,000, and the diisocyanate component constituting the polyester polyurethane resin (A) includes a diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms, thereby having excellent flame retardancy, initial and post-soldering conductivity, and also excellent heat resistance.

[0054] The present invention will be described in detail below.

[0055] Additionally, in this specification, "polyester polyurethane resin (A)", etc. is also referred to as "component (A)", etc.

[0056] <Polyester polyurethane resin (A)>

[0057] The resin composition of the present invention contains a polyester polyurethane resin (A), and the diisocyanate component constituting the polyester polyurethane resin (A) comprises a diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms.

[0058] The polyester polyurethane resin (A) may be a resin having two or more ester bonds and two or more urethane bonds, but it is preferable that it be a resin having polyester chains and two or more urethane bonds.

[0059] In addition, the polyester polyurethane resin (A) is preferably a resin formed by reacting at least a polyester polyol, a polyisocyanate, and a chain extender as raw materials, and is more preferably a resin formed by reacting at least a polyester polyol, a polyisocyanate, and a diol compound.

[0060] It is preferable that the polyester portion of the polyester polyurethane resin (A) be formed from an acid component and an alcohol component.

[0061] As for the acid component, polycarboxylic acid compounds are preferred, and dicarboxylic acid compounds are more preferred. Additionally, sulfocarboxylic acid compounds, etc., may also be used as the acid component. Furthermore, aromatic acids are preferably cited as the acid component.

[0062] As for the alcohol component, polyhydric alcohol compounds are preferred, and diol compounds are more preferred.

[0063] In addition, the polyester portion may be formed by a hydroxycarboxylic acid compound.

[0064] When the total amount of all acid components constituting the polyester portion of the polyester polyurethane resin (A) is set to 100 mol%, in terms of adhesion, heat resistance and moisture-heat resistance, among the total acid components, it is preferable that the aromatic acid is 30 mol% or more, more preferable that it is 45 mol% or more, and particularly preferable that it is 60 mol% or more.

[0065] Examples of aromatic acids include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, naphthalenedicarboxylic acid, biphenyldicarboxylic acid, and 5-hydroxyisophthalic acid. In addition, examples include aromatic dicarboxylic acids having a sulfonic acid group or a sulfonate group, such as sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, 5-(4-sulfophenoxy)isophthalic acid, sulfoterephthalic acid, their metal salts, their ammonium salts, etc., and aromatic oxycarboxylic acids such as p-hydroxybenzoic acid, p-hydroxyphenylpropionic acid, p-hydroxyphenylacetic acid, 6-hydroxy-2-naphthoic acid, 4,4-bis(p-hydroxyphenyl)valeric acid. Among these, from the perspective of adhesion, it is preferable to include terephthalic acid and / or isophthalic acid as the acid component, and it is particularly preferable that it be terephthalic acid and / or isophthalic acid.

[0066] In addition, the above acid component may be a derivative of an acid compound, such as an ester, during resin synthesis.

[0067] In addition, other acidic components include cycloaliphatic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid and their acid anhydrides, and aliphatic dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanetic acid, and dimer acid.

[0068] Meanwhile, polyhydric alcohol components preferably include aliphatic diol compounds, cycloaliphatic diol compounds, aromatic diol compounds, ether-linked diol compounds, etc.

[0069] Examples of aliphatic diol compounds include ethylene glycol, 1,2-propylene diol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, hydroxypivalate neopentyl glycol ester, dimethylolheptane, 2,2,4-trimethyl-1,3-pentanediol, etc.

[0070] Examples of cycloaliphatic diol compounds include 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, tricyclodecanediol, tricyclodecanedimethylol, spiroglycol, hydrogenated bisphenol A, ethylene oxide adducts and propylene oxide adducts of hydrogenated bisphenol A.

[0071] Examples of aromatic-containing diol compounds include glycols obtained by adding 1 to several moles of ethylene oxide or propylene oxide to two phenolic hydroxyl groups of bisphenols, such as paraxylene glycol, metaxylene glycol, orthoxylene glycol, 1,4-phenylene glycol, ethylene oxide adduct of 1,4-phenylene glycol, bisphenol A, ethylene oxide adduct of bisphenol A, and propylene oxide adduct.

[0072] Examples of diol compounds containing ether bonds include diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, neopentyl glycol ethylene oxide adduct, neopentyl glycol propylene oxide adduct, etc.

[0073] Among these diols, diols having side chains such as neopentyl glycol or 2-butyl-2-ethyl-1,3-propanediol are preferred for reasons of compatibility with epoxy resins, resins having carboxyl groups or carboxylic acid anhydride structures, and solution stability.

[0074] That is, the diol component constituting the polyester polyurethane resin (A) preferably includes a diol having a side chain for compatibility with epoxy resin, resin having a carboxyl group or carboxylic acid anhydride structure, and solution stability.

[0075] Among these, it is more preferable to include a diol having a side chain as the chain extender constituting the polyester polyurethane resin (A) in terms of compatibility with epoxy resins, resins having carboxyl groups or carboxylic acid anhydrides structures, solution stability, and conductivity. That is, it is more preferable that the polyester polyurethane resin (A) is a resin formed by reacting at least a polyester polyol, a polyisocyanate, and a diol having a side chain as raw materials, in terms of compatibility with epoxy resins, resins having carboxyl groups or carboxylic acid anhydrides structures, solution stability, and conductivity.

[0076] In a diol having a side chain, the side chain is preferably an alkyl group, and the number of carbon atoms in the alkyl group may be any of, for example, 1, 2, 3, 4, or 5. This is also true for a diol having a side chain described later.

[0077] Examples of diols having side chains include neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, and 2,2-dimethylolpropionic acid.

[0078] The polyester polyurethane resin (A) is preferably composed of at least a diol component in terms of conductivity at the beginning, after soldering, after long-term reliability testing, or after cold and hot cycle testing of the cured product obtained.

[0079] In addition, the diol component constituting the polyester polyurethane resin (A) is preferably a diol compound having a hydrocarbon group having 5 to 32 carbon atoms, more preferably a diol compound having a hydrocarbon group having 5 to 16 carbon atoms, and particularly preferably a diol compound having a hydrocarbon group having 7 to 12 carbon atoms, in terms of conductivity at the beginning, after soldering, after long-term reliability testing, or after cold-heat cycle testing of the cured product obtained.

[0080] The above diol compound having a hydrocarbon group having 5 to 32 carbon atoms is preferably a diol compound having an alicyclic structure or two or more side chains in terms of conductivity at the beginning, after soldering, after a long-term reliability test, or after a cold-heat cycle test of the obtained cured product, more preferably a diol compound having two or more side chains, and particularly preferably a diol compound having two side chains.

[0081] In addition, the diol compound having a hydrocarbon group having 5 to 32 carbon atoms may be a diol component constituting the polyester portion or a diol component constituting the polyurethane portion, but it is preferable that it be a diol component constituting the polyurethane portion in terms of conductivity at the beginning, after soldering, after long-term reliability testing or after cold-heat cycle testing of the resulting cured product.

[0082] In addition, hydroxycarboxylic acid compounds having hydroxyl and carboxyl groups in their molecular structure can also be used as polyester raw materials, and examples include 5-hydroxyisophthalic acid, p-hydroxybenzoic acid, p-hydroxyphenylalcohol, p-hydroxyphenylpropionic acid, p-hydroxyphenylacetic acid, 6-hydroxy-2-naphthoic acid, and 4,4-bis(p-hydroxyphenyl)valeric acid.

[0083] As a component constituting the polyester portion of the polyester polyurethane resin (A), for the purpose of introducing a branched backbone as needed, polycarboxylic acids and / or polyols having three or more functions in an amount of about 0.1 mol% to 5 mol% relative to the total acid component or total polyhydric alcohol component constituting the polyester portion may be copolymerized. In particular, when a cured layer is obtained by reacting with a curing agent, the concentration of terminal groups (reaction points) of the resin increases by introducing a branched backbone, thereby allowing a cured layer with a high crosslinking density to be obtained. Examples of polycarboxylic acids with three or more functions in that case include compounds such as trimellitic acid, trimesic acid, ethylene glycol bis(anhydrotrimellitate), glycerol tris(anhydrotrimellitate), trimellitic anhydride, pyromellitic anhydride (PMDA), oxydiphthalic dianhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride (BTDA), 3,3',4,4'-diphenyltetracarboxylic acid dianhydride (BPDA), 3,3',4,4'-diphenylsulfone tetracarboxylic acid dianhydride (DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic acid dianhydride (6FDA), and 2,2'-bis[(dicarboxyphenoxy)phenyl]propane dianhydride (BSAA). Meanwhile, examples of polyols with three or more functions include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. When using polycarboxylic acids and / or polyols with three or more functions, it is preferable to copolymerize in a range of preferably 0.1 mol% to 5 mol%, more preferably 0.1 mol% to 3 mol%, with respect to the total acid component or the total polyhydric alcohol component.

[0084] Acid addition of about 0.1 mol% to 10 mol% relative to the total acid component or total polyhydric alcohol component constituting the polyester portion of the polyester polyurethane resin (A) may be performed for the purpose of introducing carboxyl groups as needed. Since a decrease in molecular weight occurs due to ester exchange when monocarboxylic acid, dicarboxylic acid, or polyfunctional carboxylic acid compounds are used for acid addition, it is preferable to use acid anhydrides.

[0085] As acid anhydrides, compounds such as succinic anhydride, maleic anhydride, orthophthalic acid, 2,5-norbornendicarboxylic acid anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride (PMDA), oxydiphthalic acid dianhydride (ODPA), 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride (BTDA), 3,3',4,4'-diphenyltetracarboxylic acid dianhydride (BPDA), 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride (DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic acid dianhydride (6FDA), and 2,2'-bis[(dicarboxyphenoxy)phenyl]propane dianhydride (BSAA) may be used.

[0086] Acid addition can be performed directly in the bulk state after polyester polycondensation, or by dissolving the polyester and adding the acid. Although the reaction in the bulk state is fast, gelation may occur if acid addition is performed in large quantities, and since the reaction takes place at high temperatures, precautions such as blocking oxygen gas to prevent oxidation are required. On the other hand, acid addition in the solution state is slow, but a large amount of carboxyl groups can be stably introduced.

[0087] The polyurethane portion of the polyester polyurethane resin (A) is composed of at least a diisocyanate component.

[0088] In addition, the diisocyanate component comprises a diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms. Here, the methylene group in the hydrocarbon group may be substituted with non-reactive bonds such as -O-, -S-, -CO-, -COO-, -OCO-, etc. The amount of the diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms in the diisocyanate component is typically 70 mol% or more, preferably 90 mol% or more, and may be 100 mol%.

[0089] In addition, the polyurethane portion of the polyester polyurethane resin (A) may be composed of isocyanate components having one or more functional groups in addition to the diisocyanate components.

[0090] In the above diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms, the number of carbon atoms of the hydrocarbon group is preferably 8 to 12 and more preferably 8 to 10 from the perspective of conductivity after soldering, after long-term reliability testing, and after cold-heat cycle testing of the obtained cured product.

[0091] In addition, the diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms preferably has an alicyclic structure in terms of conductivity after soldering, after long-term reliability testing, and after cold-heat cycle testing of the obtained cured product.

[0092] In terms of adhesion, the polyester polyurethane resin (A) preferably has a diisocyanate component of 5 to 50 molar equivalents per 1 molar equivalent of the polyester portion. In other words, in terms of adhesion, the polyester polyurethane resin (A) preferably has 10 to 100 molar equivalents of urethane bonds per 1 molar equivalent of the polyester portion.

[0093] The polyisocyanate used in the manufacture of the polyester polyurethane resin (A) may be one of the following: diisocyanate, its dimer (urethdione), its trimer (isocyanurate, triol adduct, biuret), or a mixture of two or more of these. For example, diisocyanate components include diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, 1,5-naphthalene diisocyanate, 2,6-naphthalene diisocyanate, 4,4'-diisocyanate diphenyl ether, m-xylylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, methylenebis(4-cyclohexyl diisocyanate), isophorone diisocyanate, norvonane diisocyanate, norbornene diisocyanate, etc.

[0094] Among these, aliphatic or alicyclic diisocyanate compounds are preferred in terms of transparency and conductivity after soldering, long-term reliability testing, and cold-hot cycle testing of the obtained cured product, and alicyclic diisocyanate compounds are particularly preferred. In addition, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, methylenebis(4-cyclohexyl diisocyanate), or norbonandiisocyanate are preferred in terms of ease of availability and conductivity after cold-hot cycle testing, and 1,3-bis(isocyanatomethyl)cyclohexane is particularly preferred.

[0095] In manufacturing the polyester polyurethane resin (A), a chain extender may be used as needed.

[0096] Examples of chain extenders include diol compounds already described as components of the polyester portion, or compounds having one carboxyl group and two hydroxyl groups, such as dimethylolpropionic acid and dimethylolbutanoic acid.

[0097] Among these, as chain extenders, diol compounds are preferred in terms of conductivity, diol compounds having side chains are more preferred, and diol compounds having branched chains are particularly preferred.

[0098] As for the diol compound having a side chain, it is preferable to include at least one compound selected from the group consisting of neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, and 2,2-dimethylolpropionic acid in terms of conductivity, and it is particularly preferable to include at least one compound selected from the group consisting of neopentyl glycol and 2-butyl-2-ethyl-1,3-propanediol and 2,2-dimethylolpropionic acid.

[0099] Polyamino compounds may be used as chain extenders, but in one embodiment, it is preferable that the polyester polyurethane resin (A) does not contain urea bonds.

[0100] There are no particular limitations on the method for manufacturing the polyester polyurethane resin (A), and known methods may be used. For example, the polyester polyol and polyisocyanate, and if necessary, the chain extender may be added to the reaction vessel at once or in separate additions. In either case, the ratio of isocyanate groups to hydroxyl groups is preferably 0.9 or more and 1.1 or less, more preferably 0.98 or more and 1.02 or less, and particularly preferably 1, with respect to the sum of the hydroxyl groups of the polyester polyol and chain extender in the system and the sum of the isocyanate groups of the polyisocyanate. In addition, this reaction can be carried out by reacting in the presence or absence of a solvent that is inert to the isocyanate groups. Examples of such solvents include ester-based solvents (ethyl acetate, butyl acetate, ethyl butyrate, etc.), ether-based solvents (dioxane, tetrahydrofuran, diethyl ether, etc.), ketone-based solvents (cyclohexanone, methyl ethyl ketone, methyl isobutyl ketone, etc.), aromatic hydrocarbon-based solvents (benzene, toluene, xylene, etc.), and mixtures thereof, but ethyl acetate or methyl ethyl ketone is preferred from the perspective of reducing environmental burden. As for the reaction apparatus, it is not limited to a reaction can equipped with a stirring device, and a mixing and kneading device such as a kneader or a twin-screw extruder can also be used.

[0101] To promote the urethane reaction, catalysts used in conventional urethane reactions, such as tin-based catalysts (trimethyltin laurate, dimethyltin dilaurate, trimethyltin hydroxide, dimethyltin dihydroxide, stanner's octoate, etc.), lead-based catalysts (lead oleate, lead-2-ethylhexoate, etc.), and amine-based catalysts (triethylamine, tributylamine, morpholine, diazabicyclooctane, diazabicycloundecene, etc.) may be used.

[0102] The glass transition temperature (Tg) of the polyester portion of the polyester polyurethane resin (A) is preferably 40°C to 150°C, more preferably 45°C to 120°C, even more preferably 50°C to 90°C, and particularly preferably 60°C to 70°C, in terms of adhesion, conductivity, and heat resistance.

[0103] In addition, the glass transition temperature (Tg) of the polyester polyurethane resin (A) is preferably 30°C to 150°C, more preferably 40°C to 140°C, even more preferably 50°C to 90°C, and particularly preferably 60°C to 70°C, in terms of adhesion, conductivity, and heat resistance.

[0104] The number average molecular weight (Mn) of the polyester polyurethane resin (A) is preferably 5,000 to 100,000, more preferably 10,000 to 80,000, even more preferably 20,000 to 60,000, and particularly preferably 25,000 to 50,000 in terms of conductivity and heat resistance.

[0105] In addition, the values ​​of the number average molecular weight (Mn) and weight average molecular weight (Mw) of the resin in the present invention can be obtained by gel permeation chromatography (GPC).

[0106] In the polyester polyurethane resin (A), the molecular weight per urethane bond is preferably 200 to 8,000 in terms of conductivity and heat resistance, more preferably 200 to 5,000, even more preferably 300 to 2,000, particularly preferably 400 to 1,500, and most preferably 700 to 1,000.

[0107] For example, in the case of polyester polyurethane resin (A), if there are 40 urethane bonds per molecule and the number average molecular weight is 32,000, then 32,000 / 40 = 800, and the molecular weight per urethane bond is 800. In this way, if the polyester polyurethane resin (A) has X urethane bonds per molecule and the number average molecular weight is Y, then the molecular weight per urethane bond in the polyester polyurethane resin (A) is Y / X. When calculated from the raw material composition, the number of moles of isocyanate groups reacted with 1 mole of polyester polyol, which is the raw material of the polyester polyurethane resin (A), may be considered as the "number of urethane bonds in the polyester polyurethane resin (A)."

[0108] The acid value of the polyester polyurethane resin (A) is preferably 0 mgKOH / g to 50 mgKOH / g in terms of adhesion and conductivity, more preferably 0.1 mgKOH / g to 20 mgKOH / g, even more preferably 0.1 mgKOH / g to 5 mgKOH / g, and particularly preferably 1.0 mgKOH / g to 5.0 mgKOH / g.

[0109] In addition, the acid value of the polyester polyurethane resin (A) is preferably 20 mgKOH / g or less from the perspective of heat resistance, and is particularly preferably 5.0 mgKOH / g or less.

[0110] The method for measuring the acid value of a resin in the present invention is to determine the acid value by using a phenolphthalein solution as an indicator and neutralizing the sample with a potassium hydroxide benzyl alcohol solution.

[0111] Among these, the polyester polyurethane resin (A) is preferably a polyester polyurethane resin having a polyester structure with a number average molecular weight of 1,000 to 50,000 in terms of adhesion, conductivity and heat resistance, more preferably a polyester polyurethane resin having a polyester structure with a number average molecular weight of 2,000 to 40,000, even more preferably a polyester polyurethane resin having a polyester structure with a number average molecular weight of 3,000 to 30,000, particularly preferably a polyester polyurethane resin having a polyester structure with a number average molecular weight of 8,000 to 30,000, and most preferably a polyester polyurethane resin having a polyester structure with a number average molecular weight of 15,000 to 30,000.

[0112] The resin composition of the present invention may contain one type of polyester polyurethane resin (A) alone, or may contain two or more types.

[0113] The content of the polyester polyurethane resin (A) is preferably 5% to 90% by mass with respect to the total solid content of the resin composition, with respect to adhesion, conductivity and heat resistance, more preferably 10% to 80% by mass, even more preferably 20% to 75% by mass, and particularly preferably 30% to 70% by mass.

[0114] In addition, regarding adhesion, conductivity, and heat resistance, the content of the polyester polyurethane resin (A) is preferably 5% to 90% by mass with respect to the total amount of the polyester polyurethane resin (A), epoxy resin (B), resin (C) having a carboxyl group or carboxylic acid anhydride structure, and imidazole silane compound (D) which may be included as an optional component in the resin composition, it is more preferable to be 10% to 90% by mass, even more preferable to be 10% to 70% by mass, and particularly preferable to be 30% to 70% by mass.

[0115] <Epoxy resin(B)>

[0116] The resin composition of the present invention contains epoxy resin (B).

[0117] The epoxy resin (B) is a component that provides adhesion or heat resistance in the cured portion after adhesion. The epoxy resin (B) in the present invention includes not only high-molecular-weight compounds having epoxy groups but also low-molecular-weight compounds having epoxy groups. It is preferable that the number of epoxy groups in the epoxy resin (B) be two or more.

[0118] As an epoxy resin (B), for example, glycidyl esters such as orthophthalate diglycidyl ester, isophthalate diglycidyl ester, terephthalate diglycidyl ester, p-hydroxybenzoate diglycidyl ester, tetrahydrophthalate diglycidyl ester, succinate diglycidyl ester, adipicate diglycidyl ester, sebacate diglycidyl ester, trimellitic acid triglycidyl ester; Examples include glycidyl ethers such as bisphenol A diglycidyl ether and its oligomer, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, tetraphenylglycidyl ether ethane, triphenylglycidyl ether ethane, polyglycidyl ether of sorbitol, polyglycidyl ether of polyglycerol, etc.; and novolak-type epoxy resins such as phenol novolak epoxy resin, o-cresol novolak epoxy resin, bisphenol A novolak epoxy resin, etc.

[0119] In addition, brominated bisphenol A type epoxy resin with flame retardancy, phosphorus-containing epoxy resin, dicyclopentadiene backbone-containing epoxy resin, naphthalene backbone-containing epoxy resin, anthracene type epoxy resin, tertiary butylcatechol type epoxy resin, biphenyl type epoxy resin, and bisphenol S type epoxy resin can also be used.

[0120] Among them, the epoxy resin (B) preferably comprises a bisphenol A type epoxy resin and / or a novolak type epoxy resin in terms of adhesion and heat resistance.

[0121] In the present invention, in order to exhibit high heat resistance after curing, it is preferable that the epoxy resin (B) comprises a compound having three or more epoxy groups in one molecule. When such a compound is used, the crosslinking reactivity with the polyester urethane resin (A) and the resin (C) having a carboxyl group or carboxylic acid anhydride structure is increased compared to the case where an epoxy resin having two epoxy groups is used, and sufficient heat resistance is obtained.

[0122] In the epoxy resin (B), the content of a compound having three or more epoxy groups per molecule is preferably 15 mass% or more with respect to the total mass of the epoxy resin (B) for the sake of heat resistance, more preferably 20 mass% or more, and particularly preferably 25 mass% or more.

[0123] The resin composition of the present invention may contain one type of epoxy resin (B) alone, or may contain two or more types.

[0124] The content of the epoxy resin (B) is preferably 1% to 60% by mass with respect to the total amount of the polyester polyurethane resin (A), epoxy resin (B), resin (C) having a carboxyl group or carboxylic acid anhydride structure, and imidazole silane compound (D) which may be included as an optional component in the resin composition, in terms of adhesion, conductivity, and heat resistance, and is more preferably 2% to 40% by mass, and particularly preferably 3% to 20% by mass.

[0125] <Resin (C) having a carboxyl group or carboxylic acid anhydride structure>

[0126] The resin composition of the present invention preferably contains a resin (C) having a carboxyl group or carboxylic acid anhydride structure, in terms of conductivity after soldering, after long-term reliability testing, and after cold-heat cycle testing of the obtained cured product.

[0127] A resin (C) having a carboxyl group or carboxylic acid anhydride structure is preferably solid at 25°C.

[0128] A resin (C) having a carboxyl group or carboxylic acid anhydride structure is not particularly limited as long as it is a resin soluble in the organic solvent described below, and specific examples include polyamide resin, polyolefin resin, acrylic resin, copolymers thereof.

[0129] Among these, the resin (C) having a carboxyl group or carboxylic acid anhydride structure is preferably selected from the group consisting of polyamide resins, polyolefin resins, and copolymers thereof, in terms of conductivity after soldering, after long-term reliability testing, and after cold-heat cycle testing of the obtained cured product, more preferably includes at least one of a polyamide resin having an acid value and a resin having an acid-modified polyolefin structure, and particularly preferably includes a polyamide resin having an acid value.

[0130] The polyamide resin is a condensation resin obtained using a dibasic acid and a diamine as monomers, and preferably, is a resin obtained using two or more types of dibasic acids and two or more types of diamines. Specifically, examples of the dibasic acids include adipic acid, sebacic acid, azelaic acid, undecane diacid, dodecane diacid, dimer acid, isophthalic acid, terephthalic acid, sodium 5-sulfoisophthalate, etc. In addition, specifically examples of the diamines include hexamethylenediamine, heptamethylenediamine, p-diaminomethylcyclohexane, bis(p-aminocyclohexyl)methane, m-xylenediamine, piperazine, isophoronediamine, etc.

[0131] Polyamide resins may be block copolymers.

[0132] In the above diamine component, it is desirable to include piperazine for the reason of improving adhesion. When the total amount of diamine components constituting the resin (C) having a carboxyl group or carboxylic acid anhydride structure is set to 100 mol%, it is desirable to include 1.0 mol% or more of piperazine, and more desirable to include 20 mol% or more.

[0133] Polyamide resins, particularly those comprising constituent units derived from aliphatic dibasic acids and alicyclic diamines, exhibit excellent solubility in solvents. Furthermore, adhesive compositions containing such polyamide resins are desirable because they show almost no increase in viscosity even after long-term storage and exhibit good adhesion to a wide range of substrates.

[0134] The polyamide resin may appropriately include constituent units derived from aminocarboxylic acids, lactams, etc. Specifically, examples of the above aminocarboxylic acids include 11-aminoundecanic acid, 12-aminododecanoic acid, 4-aminomethylbenzoic acid, 4-aminomethylcyclohexanecarboxylic acid, etc., and examples of lactams include ε-caprolactamic acid, ω-laurolactamic acid, α-pyrrolidone, α-piperidone, etc.

[0135] In addition, the polyamide resin may appropriately include structural units derived from polyalkylene glycol for the purpose of imparting flexibility. Specifically, examples of the polyalkylene glycol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, block or random copolymers of ethylene oxide and propylene oxide, block or random copolymers of ethylene oxide and tetrahydrofuran, etc. Structural units derived from polyalkylene glycol may be included alone or may be included in two or more types.

[0136] The polyamide resin may have a composition such as, for example, nylon 6 / nylon 66 copolymer, nylon 6 / nylon 6-10 copolymer, nylon 6 / nylon 66 / nylon 6-10 copolymer, nylon 6 / nylon 66 / nylon 11 copolymer, nylon 6 / nylon 66 / nylon 12 copolymer, nylon 6 / nylon 6-10 / nylon 6-11 copolymer, nylon 6 / nylon 11 / isophoronediamine copolymer, nylon 6 / nylon 66 / nylon 6 copolymer, nylon 6 / nylon 6-10 / nylon 12 copolymer, etc.

[0137] Next, the modified polyamide resin is an alcohol-soluble nylon resin produced by adding formaldehyde and alcohol to an unmodified polyamide resin and introducing an alkoxymethyl group to the nitrogen atoms constituting the amide bonds. Specifically, examples include modified polyamide resins in which 6-nylon, 66-nylon, etc., have been alkoxymethylated. Furthermore, the introduction of N-alkoxymethyl groups contributes to lowering the melting point, increasing flexibility, and improving solubility in solvents, and the introduction rate is appropriately set according to the purpose.

[0138] Examples of resins having a polyolefin structure include polyethylene, polypropylene, polybutene, and copolymers thereof, although there are no particular limitations. Additionally, the resin having a polyolefin structure may be a copolymer of an olefin and another ethylenically unsaturated compound, or a block copolymer of a polyolefin and a polycondensation resin. For example, the resin having a polyolefin structure may be a styrene-based resin such as a styrene-butadiene copolymer, a styrene-butadiene-styrene block copolymer, a styrene-ethylene / propylene-styrene block copolymer, a styrene-ethylene / butylene-styrene block copolymer, a styrene-isoprene / butadiene-styrene block copolymer, or a styrene-isoprene-styrene block copolymer.

[0139] Among them, the resin having an acid-modified polyolefin structure is preferably an acid-modified polyolefin resin.

[0140] In addition, there are no particular limitations on the method of introducing a carboxyl group or a carboxylic acid anhydride structure into the above-mentioned polyamide resin and a resin having a polyolefin structure, but examples include copolymerizing an unsaturated carboxylic acid anhydride and modifying the resin with a carboxylic acid anhydride. Specifically, examples include a resin formed by graft polymerizing an unsaturated carboxylic acid anhydride, such as maleic anhydride, itaconic anhydride, acrylic acid, or methacrylic acid, onto a polyolefin resin such as polypropylene; a polyamide resin having an acid terminal obtained by reacting a dibasic acid in excess with a diamine; a resin obtained by reacting a polyamide resin with a carboxylic acid anhydride; and a polyamide resin using a compound having two or more carboxylic acid anhydride structures, such as pyromellitic anhydride, as the carboxylic acid component of the raw material.

[0141] The acid value of the resin (C) having a carboxyl group or a carboxylic acid anhydride structure is at least 0.1 mg KOH / g to 200 mg KOH / g, which is not particularly limited, but is more preferably 1 mg KOH / g to 100 mg KOH / g, even more preferably 2 mg KOH / g to 50 mg KOH / g, and particularly preferably 5 mg KOH / g to 30 mg KOH / g.

[0142] The amine value of the resin (C) having a carboxyl group or carboxylic acid anhydride structure is not particularly limited. Generally, if the amine value of the polyamide resin is high, the reaction between the amino group and the epoxy group is rapid, and good curability is obtained with heat treatment over a short period of time; however, on the other hand, the reaction proceeds slowly immediately after mixing the resin (C) having a carboxyl group or carboxylic acid anhydride structure and the epoxy resin (B), causing the viscosity of the composition to increase significantly or gel. Therefore, curability and stability can be achieved by selecting the amine value of the resin (C) having a carboxyl group or carboxylic acid anhydride structure. The preferred range for the amine value of the resin (C) having a carboxyl group or carboxylic acid anhydride structure is 1 mgKOH / g to 6 mgKOH / g.

[0143] In addition, the melting point of the resin (C) having a carboxyl group or carboxylic acid anhydride structure is not particularly limited, but is preferably in the range of 50°C to 220°C and more preferably in the range of 70°C to 180°C in terms of solubility in solvents and heat resistance of the cured product.

[0144] Examples of solvents for dissolving a resin (C) having a carboxyl group or a carboxylic acid anhydride structure include alcohols such as methanol, ethanol, isopropyl alcohol, n-propyl alcohol, isobutyl alcohol, n-butyl alcohol, benzyl alcohol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, and diacetone alcohol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, and isophorone; aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and mesitylene; and esters such as methyl acetate, ethyl acetate, ethylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate. These solvents may be used individually or in combination of two or more.

[0145] The resin composition of the present invention may contain one type of resin (C) having a carboxyl group or a carboxylic acid anhydride structure, or may contain two or more types.

[0146] The content of the resin (C) having a carboxyl group or carboxylic acid anhydride structure is preferably 5% to 90% by mass with respect to the total amount of the polyester polyurethane resin (A), epoxy resin (B), the resin (C) having a carboxyl group or carboxylic acid anhydride structure, and the imidazole silane compound (D) which may be included as an optional component in the resin composition, in terms of adhesion, conductivity, and heat resistance, it is more preferable to have 5% to 70% by mass, and particularly preferable to have 30% to 50% by mass.

[0147] In addition, in the resin composition of the present invention, with respect to adhesion, conductivity, and heat resistance, with respect to the total amount of polyester polyurethane resin (A), epoxy resin (B), resin having a carboxyl group or carboxylic acid anhydride structure (C), and imidazole silane compound (D) which may be included as an optional component in the resin composition, it is preferable that the content of polyester polyurethane resin (A) is 10 mass% to 90 mass%, and the content of resin having a carboxyl group or carboxylic acid anhydride structure (C) is 5 mass% to 70 mass%.

[0148] In addition, in the resin composition of the present invention, with respect to adhesion, conductivity, and heat resistance, the content of the resin (C) having a carboxyl group or carboxylic acid anhydride structure is preferably 1 to 100 parts by mass with respect to 100 parts by mass of polyester polyurethane resin (A), preferably 20 to 100 parts by mass, more preferably 50 to 95 parts by mass, and particularly preferably 70 to 90 parts by mass.

[0149] In addition, the content of the resin (C) having a carboxyl group or carboxylic acid anhydride structure is preferably less than or equal to the content of the polyester polyurethane resin (A) in terms of adhesion, conductivity, and heat resistance, and is more preferably less than the content of the polyester polyurethane resin (A).

[0150] In the above resin composition, the content of the polyester polyurethane resin (A) and the resin (C) having a carboxyl group or carboxylic acid anhydride structure is preferably 50% to 98% by mass with respect to the total amount of the polyester polyurethane resin (A), epoxy resin (B), the resin (C) having a carboxyl group or carboxylic acid anhydride structure, and the imidazole silane compound (D) which may be included as an optional component, in terms of adhesion, conductivity, and heat resistance. It is more preferably 70% to 97% by mass, and particularly preferably 75% to 95% by mass.

[0151] <Imidazolesilane compound (D)>

[0152] The resin composition of the present invention preferably contains an imidazole silane compound (D) in terms of conductivity and adhesion.

[0153] The imidazole silane compound (D) is a compound having one or more imidazole ring structures and one or more silane structures, and is presumed to act as a curing agent for the epoxy resin (B).

[0154] The imidazole silane compound (D) is preferably a compound having one imidazole ring structure and one silyl group in terms of conductivity and adhesion.

[0155] In addition, as for the imidazole silane compound (D), a compound represented by the following formula (D) or its acid adduct may be preferably cited in terms of conductivity and adhesion.

[0156] [Chemical Formula 1]

[0157]

[0158] In equation (D), R 1 and R 2 Each independently represents a hydrogen atom, a saturated hydrocarbon group, an unsaturated hydrocarbon group, or an aryl group, and each of the said groups may have a substituent, and R 3 and R 4 Each independently represents a hydrogen atom or an alkyl group, and R 3 At least one of them is an alkyl group, said alkyl group may have a substituent, n represents an integer from 1 to 3, and R 5 represents a group in which an alkylene group, or a part of an alkylene group, is substituted with at least one of formulas (D2) to (D5).

[0159] [Chemical Formula 2]

[0160]

[0161] Among equations (D2), (D3) and (D5), R 6 represents a hydrogen atom or a hydroxyl group, and R 7 represents a hydrogen atom, an alkyl group, or an aryl group, and R 8 and R 9 Each represents independently a hydrogen atom, an alkyl group, or an aryl group, and each of the above groups may have a substituent, and the dashed portion indicates a bonding position with other structures.

[0162] When containing an imidazole silane compound (D), particularly a compound represented by the above formula (D), adhesion to metal, particularly plated copper foil, is improved. This is presumed to be because the silane structure and the imidazole ring structure exhibit high affinity with either the metal surface or the resin (C) having a carboxyl group or carboxylic acid anhydride structure, and thus the adhesion is improved through their interaction. Additionally, since the imidazole ring structure can also react with the epoxy resin (B), it is presumed that this adhesion-enhancing effect can be maintained even in the reflow process described later.

[0163] It is preferable that the imidazolesilane compound (D) is a compound having an imidazole ring structure as a first functional group and an alkoxysilyl group as a second functional group in one molecule.

[0164] The imidazole ring in the above imidazole ring structure may have substituents such as saturated hydrocarbon groups or unsaturated hydrocarbon groups.

[0165] In equation (D), R 1 , R 2 , R 3 and R 4 When the group is an alkyl group, the preferred number of carbon atoms is 1 to 3.

[0166] Examples of imidazole ring structures constituting the imidazole silane compound (D) include imidazole ring structures, 2-alkylimidazole ring structures, 2,4-dialkylimidazole ring structures, and 4-vinylimidazole ring structures.

[0167] In the imidazole silane compound (D), it is preferable that the alkoxysilyl group and the imidazole ring structure are bonded through a group in which an alkylene group, or a part of an alkylene group, is substituted with at least one of formulas (D2) to (D5).

[0168] R of Equation (D) 5 In the above, the number of carbon atoms in the alkylene group is preferably 1 to 10, and more preferably 3 to 7.

[0169] The imidazole silane compound (D) can be suitably synthesized by, for example, by the reaction of an imidazole compound and a 3-glycidoxyalkylsilane compound.

[0170] In addition, the imidazole silane compound (D) may be a silanol compound produced by the hydrolysis of an alkoxysilyl group, a polyorganosiloxane compound produced by the dehydration condensation reaction of a silanol compound, or a mixture thereof.

[0171] In addition, acids added to the compound represented by formula (D) may include acetic acid, lactic acid, salicylic acid, benzoic acid, adipic acid, phthalic acid, citric acid, tartaric acid, maleic acid, trimellitic acid, phosphoric acid, and isocyanuric acid. These may be used individually or in combination of two or more.

[0172] In addition, as for the imidazole silane compound (D), it is more preferable that it be a compound represented by the following formula (D6) or formula (D7), or an acid adduct thereof, in terms of conductivity and adhesion.

[0173] [Chemical Formula 3]

[0174]

[0175] Among equations (D6) and (D7), R 1 and R 2 Each independently represents a hydrogen atom, a saturated hydrocarbon group, an unsaturated hydrocarbon group, or an aryl group, and each of the said groups may have a substituent, and R 3 and R 4 Each independently represents a hydrogen atom or an alkyl group, and R 3 At least one of them is an alkyl group, said alkyl group may have a substituent, n represents an integer from 1 to 3, and R 5' represents an alkylene group, and R 6 It represents a hydrogen atom or a hydroxyl group.

[0176] R of equations (D6) and (D7) 5' The number of carbon atoms in the alkylene group is preferably 1 to 10, and more preferably 3 to 7.

[0177] Specific examples of imidazole silane compounds (D) include 1-(2-hydroxy-3-trimethoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-triethoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-tripropoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-tributoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-triethoxysilylpropoxypropyl)-2-methylimidazole, 1-(2-hydroxy-3-triethoxysilylpropoxypropyl)-4-methylimidazole, 1-(3-oxo-4-trimethoxysilylpropoxypropyl)imidazole, 1-(3-trimethoxysilylpropylamino)imidazole, etc. It is possible.

[0178] Among these, the compound represented by the above formula (D6) or formula (D7) or its acid adduct is preferred because it has good heat resistance and good solubility in solvents, and the acid adduct of the compound represented by formula (D6) is more preferred.

[0179] The compound represented by the above formula (D6) can be suitably obtained by reacting an imidazole compound, such as imidazole, 2-alkylimidazole, 2,4-dialkylimidazole, or 4-vinylimidazole, with a 3-glycidoxypropylsilane compound, such as 3-glycidoxypropyltrialkoxysilane, 3-glycidoxypropyldialkoxyalkylsilane, or 3-glycidoxypropylalkoxydialkylsilane. Among these, a particularly preferred product is the reaction product of imidazole and 3-glycidoxypropyltrimethoxysilane.

[0180] The compound represented by the above formula (D7) can be suitably obtained by reacting an imidazole compound with 3-methacryloyloxypropyltrimethoxysilane, etc.

[0181] The resin composition of the present invention may contain one type of imidazole silane compound (D) alone, or may contain two or more types.

[0182] The content of the imidazole silane compound (D) is preferably 0.05 mass% to 20 mass% with respect to the total amount of the polyester polyurethane resin (A), epoxy resin (B), resin (C) having a carboxyl group or carboxylic acid anhydride structure, and imidazole silane compound (D) in the resin composition, in terms of conductivity and adhesion, more preferably 0.1 mass% to 10 mass%, and particularly preferably 1 mass% to 5 mass%.

[0183] <Weapon Filler(E)>

[0184] The resin composition of the present invention preferably contains an inorganic filler (E) in terms of the elongation of the cured product obtained, and the conductivity of the cured product obtained at the initial stage, after soldering, after long-term reliability testing, and after cold and hot cycle testing, and more preferably contains the inorganic filler (E) and the organic filler (F) described below.

[0185] In addition, the inorganic filler (E) in this specification is a filler made of metal or an alloy thereof, that is, an inorganic filler other than the metal filler (G) described later.

[0186] As for the inorganic filler (E), there are no particular limitations, but examples include non-conductive inorganic fillers such as calcium carbonate particles, titanium oxide particles, aluminum oxide particles, zinc oxide particles, talc particles, silica particles, and conductive inorganic fillers such as carbon black particles.

[0187] Among these, at least one particle selected from the group consisting of talc particles and silica particles is preferred in terms of conductivity of the obtained cured product at the initial stage, after soldering, after long-term reliability testing, and after cold and hot cycle testing, and talc particles are more preferred.

[0188] The average particle diameter of the inorganic filler (E) is not particularly limited, but is preferably 0.001 μm to 50 μm in terms of conductivity, applicability, and thickness control of the cured product obtained at the beginning, after soldering, after long-term reliability testing, and after cold-heat cycle testing, more preferably 0.005 μm to 30 μm, and particularly preferably 0.01 μm to 10 μm.

[0189] In addition, the average particle diameter of the filler in this specification is the D50 average particle diameter obtained by measuring the filler in the tornado dry powder sample module using a laser diffraction-scattering particle size distribution measuring device LS 13320 (manufactured by Beckman Coulter, Inc.), and the average particle diameter of the particle size at which the particle integration value is 50% was used.

[0190] The resin composition of the present invention may contain one type of inorganic filler (E) alone or two or more types, but it is preferable to contain two or more types in terms of conductivity of the cured product obtained at the initial stage, after soldering, after long-term reliability testing, and after cold-heat cycle testing, and it is more preferable to contain two types.

[0191] The content of the inorganic filler (E) is preferably 0.1 to 50 parts by mass per 100 parts by mass of the total amount of the polyester polyurethane resin (A), epoxy resin (B), resin (C) having a carboxyl group or carboxylic acid anhydride structure, and an imidazole silane compound (D) that may be included as an optional component, in terms of adhesion, conductivity, and curability, and is more preferably 0.5 to 20 parts by mass, and particularly preferably 1 to 10 parts by mass.

[0192] <Organic Filler(F)>

[0193] The resin composition of the present invention preferably contains an organic filler (F) in terms of the elongation, conductivity, and moisture-heat resistance of the resulting cured product. The organic filler (F) is typically composed mainly of resin and is non-conductive.

[0194] Examples of organic fillers (F) include (meth)acrylic resin particles, polybutadiene particles, nylon microparticles, polyolefin particles, polyester particles, polycarbonate particles, polyvinyl alcohol particles, polyvinyl ether particles, polyvinyl butyral particles, silicone rubber particles, polyurethane particles, phenolic resin particles, polytetrafluoroethylene particles, etc.

[0195] It was discovered that when an organic filler is dissolved with a polyester polyurethane resin (A), an epoxy resin (B), and a resin (C) having a carboxyl group or carboxylic acid anhydride structure, it has the effect of increasing the compatibility of these resins. Furthermore, in order to further improve the compatibility or liquid stability of these resins, silicone particles, polybutadiene particles, (meth)acrylic resin particles, or polyurethane particles are particularly preferred.

[0196] The average particle diameter of the organic filler (F) is not particularly limited, but from the perspective of applicability and controllability of the application thickness, it is preferably 0.5 μm to 50 μm, and more preferably 1 μm to 30 μm.

[0197] The resin composition of the present invention may contain one type of organic filler (F) alone, or may contain two or more types.

[0198] The content of the organic filler (F) is preferably 1 to 50 parts by mass with respect to 100 parts by mass of the total amount of the polyester polyurethane resin (A), epoxy resin (B), resin (C) having a carboxyl group or carboxylic acid anhydride structure, and an imidazole silane compound (D) that may be included as an optional component in the resin composition, in terms of adhesion, conductivity, and curability, and is more preferably 5 to 40 parts by mass, and particularly preferably 10 to 20 parts by mass.

[0199] <Metal Filler (G)>

[0200] The resin composition of the present invention preferably contains a metal filler (G) for the sake of conductivity and heat resistance. The metal filler (G) is typically conductive.

[0201] As the metal filler (G), metal particles made of conductive metals such as gold, platinum, silver, copper, and nickel, or alloys thereof, are preferably used. In addition, rather than particles of a single composition, particles formed by using a metal or resin as a core and forming a coating layer of a highly conductive material are also preferred from the perspective of cost reduction. The core is preferably made of at least one material selected from the group consisting of nickel, silica, copper, and resin, and is more preferably made of a conductive metal or an alloy thereof. The coating layer is preferably a layer made of a material with excellent conductivity, and is preferably a layer made of a conductive metal or a conductive polymer.

[0202] Conductive metals include, for example, gold, platinum, silver, tin, manganese, and indium, and their alloys. Additionally, conductive polymers include polyaniline and polyacetylene. Among these, silver is preferred in terms of conductivity.

[0203] The particle comprising the above-mentioned nucleus and coating layer preferably has a coating layer in a ratio of 1 to 40 parts by mass per 100 parts by mass of nucleus, and more preferably has a coating layer in a ratio of 5 to 30 parts by mass, from the perspective of cost and conductivity.

[0204] The particle composed of the above-mentioned nucleus and coating layer is preferably a particle in which the coating layer completely covers the nucleus. However, in practice, there are cases where a part of the nucleus is exposed. Even in such cases, if the conductive material covers 70% or more of the surface area of ​​the nucleus, it is easy to maintain conductivity.

[0205] The shape of the metal filler (G) is not limited to any shape, provided that the desired conductivity is obtained. Specifically, for example, a spherical shape, a flake shape, a leaf shape, a branch shape, a plate shape, a needle shape, a rod shape, or a grape shape is preferred.

[0206] The average particle diameter of the metal filler (G) is preferably 1 μm to 100 μm in terms of conductivity and storage stability, more preferably 3 μm to 50 μm, and particularly preferably 4 μm to 15 μm.

[0207] In addition, the average particle diameter of the metal filler (G) may be obtained from the average of approximately 20 particles randomly selected from an electron microscope magnified image (about 1,000 to 10,000 times), in addition to the method described above. In this case, the average particle diameter is preferably 1 μm to 100 μm, and more preferably 3 μm to 50 μm. Furthermore, if the metal filler (G) has a major axis direction and a minor axis direction (e.g., rod-shaped particles), the average particle diameter is calculated based on the length of the major axis direction.

[0208] The resin composition of the present invention may contain one type of metal filler (G) alone, or two or more types.

[0209] The content of the metal filler (G) is preferably 1 to 500 parts by mass with respect to 100 parts by mass of the total amount of the polyester polyurethane resin (A), epoxy resin (B), and resin (C) having a carboxyl group or carboxylic acid anhydride structure in the resin composition, in terms of conductivity, heat resistance, and storage stability, more preferably 10 to 350 parts by mass, and particularly preferably 10 to 50 parts by mass.

[0210] The resin composition of the present invention may contain other additives in addition to the aforementioned components.

[0211] Other additives, other thermoplastic resins, tackifiers, flame retardants, curing agents, curing accelerators, coupling agents, thermal aging inhibitors, leveling agents, defoaming agents, and solvents other than those mentioned above, may be included in an amount that does not affect the function of the resin composition.

[0212] Examples of the above other thermoplastic resins include phenoxy resin, polyester resin, polycarbonate resin, polyphenylene oxide resin, polyurethane resin, polyacetal resin, polyethylene-based resin, polypropylene-based resin, and polyvinyl-based resin. These thermoplastic resins may be used as a single type or two or more types may be used in combination.

[0213] Examples of the above tackifiers include coumarone-indene resin, terpene resin, terpene-phenol resin, rosin resin, pt-butylphenol-acetylene resin, phenol-formaldehyde resin, xylene-formaldehyde resin, petroleum-based hydrocarbon resin, hydrogenated hydrocarbon resin, turpentine-based resin, etc. These tackifiers may be used alone or in combination of two or more types.

[0214] The above flame retardant may be either an organic flame retardant or an inorganic flame retardant.

[0215] Organic flame retardants include, for example, phosphorus-based flame retardants such as melamine phosphate, polymelamine phosphate, guanidine phosphate, polyguanidine phosphate, ammonium phosphate, ammonium phosphate amide, ammonium phosphate amide, carbamate phosphate, polycarbamate phosphate, aluminum trisdiethylphosphinate, aluminum trismethylethylphosphinate, aluminum trisdiphenylphosphinate, zinc bisdiethylphosphinate, zinc bismethylethylphosphinate, zinc bisdiphenylphosphinate, titanyl bisdiethylphosphinate, titanium tetrakisdiethylphosphinate, titanyl bismethylethylphosphinate, titanium tetrakisdiphenylphosphinate, titanium bisdiphenylphosphinate, titanium bisdiphenylphosphinate, and titanium tetrakisdiphenylphosphinate; Examples include triazine-based compounds such as melamine, melam, and melamine cyanurate, nitrogen-based flame retardants such as cyanuric acid compounds, isocyanuric acid compounds, triazole-based compounds, tetrazole compounds, diazo compounds, and urea; silicon-based flame retardants such as silicon compounds and silane compounds.

[0216] In addition, inorganic flame retardants may include metal hydroxides such as aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, barium hydroxide, and calcium hydroxide; metal oxides such as tin oxide, aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, molybdenum oxide, and nickel oxide; zinc carbonate, magnesium carbonate, calcium carbonate, barium carbonate, zinc borate, and hydrated glass.

[0217] These flame retardants may be used as a single type or in combination of two or more types.

[0218] The above curing agent is a component for forming a cross-linked structure by reaction with the epoxy resin (B), and examples include amine-based curing agents such as aliphatic diamines, aliphatic polyamines, cyclic aliphatic diamines and aromatic diamines, polyamideamine-based curing agents, acid-based curing agents such as aliphatic polycarboxylic acids, alicyclic polycarboxylic acids, aromatic polycarboxylic acids and their acid anhydrides; basic active hydrogen-based curing agents such as dicyandiamide or organic acid dihydrazide; polymericaptan-based curing agents; novolak resin-based curing agents; urea resin-based curing agents; melamine resin-based curing agents, etc.

[0219] These curing agents may be used as a single type or in combination of two or more types.

[0220] Examples of aliphatic diamine-based curing agents include ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, polymethylenediamine, polyetherdiamine, 2,5-dimethylhexamethylenediamine, trimethylhexamethylenediamine, etc.

[0221] Examples of aliphatic polyamine-based curing agents include diethylenetriamine, iminobis(hexamethylene)triamine, trihexatetramine, tetraethylenepentamine, aminoethylethanolamine, tri(methylamino)hexane, dimethylaminopropylamine, diethylaminopropylamine, methyliminobispropylamine, etc.

[0222] Examples of cyclic aliphatic diamine-based curing agents include menthendiamine, isophoronediamine, bis(4-amino-3-methyldicyclohexyl)methane, diaminodicyclohexylmethane, bis(aminomethyl)cyclohexane, N-ethylaminopiperazine, 3,9-bis(3-aminopropyl)2,4,8,10-tetraoxaspiro[5.5]undecane, and water additives of methaxylylenediamine.

[0223] Examples of aromatic diamine-based curing agents include metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, diaminodiethyldiphenylmethane, and metaxylylenediamine.

[0224] Examples of aliphatic polycarboxylic acid-based curing agents and acid anhydride-based curing agents include succinic acid, adipic acid, dodecenyl anhydride succinic acid, polyadipic anhydride, polyazellaic anhydride, polysebacid anhydride, etc.

[0225] Examples of alicyclic polycarboxylic acid-based curing agents and acid anhydride-based curing agents include methyltetrahydrophthalic acid, methylhexahydrophthalic acid, methylhymic acid, hexahydrophthalic acid, tetrahydrophthalic acid, trialkyltetrahydrophthalic acid, methylcyclodicarboxylic acid and their acid anhydrides.

[0226] Examples of aromatic polycarboxylic acid-based curing agents and acid anhydride-based curing agents include phthalic acid, trimellitic acid, pyromellitic acid, benzophenone tetracarboxylic acid, ethylene glycol glycol bistrimellitic acid, glycerol tritrimellitic acid and their acid anhydrides.

[0227] Examples of polymer mercaptan-based curing agents include mercaptogenic epoxy resins and mercaptopropionic acid esters.

[0228] Examples of novolak-based curing agents include phenol novolak-based curing agents and cresol novolak-based curing agents.

[0229] When the resin composition of the present invention contains the curing agent, the content of the curing agent is set such that, with respect to adhesion and heat resistance, the functional group equivalent is preferably in the range of 0.2 molar equivalents to 2.5 molar equivalents, more preferably in the range of 0.4 molar equivalents to 2.0 molar equivalents, with respect to 1 molar equivalent of the epoxy group of the epoxy resin (B).

[0230] The above curing accelerator is a component used to promote the reaction of the epoxy resin (B), and may use tertiary amine-based curing accelerators, tertiary amine salt-based curing accelerators, and imidazole-based curing accelerators.

[0231] These curing accelerators may be used as a single type or in combination of two or more types.

[0232] Examples of tertiary amine-based curing accelerators include benzyldimethylamine, 2-(dimethylaminomethyl)phenol, 2,4,6-tris(dimethylaminomethyl)phenol, tetramethylguanidine, triethanolamine, N,N'-dimethylpiperazine, triethylenediamine, and 1,8-diazabicyclo[5.4.0]undecene.

[0233] Examples of tertiary amine salt-based curing accelerators include the formate, octylate, p-toluenesulfonate, o-phthalate, phenol salt, or phenol novolak resin salt of 1,8-diazabicyclo[5.4.0]undecene, or the formate, octylate, p-toluenesulfonate, o-phthalate, phenol salt, or phenol novolak resin salt of 1,5-diazabicyclo[4.3.0]nonene.

[0234] As imidazole-based curing accelerators, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-methyl-4-ethylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, Examples include 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, etc.

[0235] When the resin composition of the present invention contains a curing accelerator, the content of the curing accelerator is preferably in the range of 1 to 10 parts by mass, and particularly preferably in the range of 2 to 5 parts by mass, with respect to adhesion and heat resistance, with respect to 100 parts by mass of epoxy resin (B).

[0236] In addition, the above coupling agents may include silane-based coupling agents such as vinyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, and imidazolesilane; titanate-based coupling agents; aluminate-based coupling agents; zirconium-based coupling agents, etc. These may be used individually or in combination of two or more types.

[0237] Examples of the above-mentioned anti-thermal aging agents include phenolic antioxidants such as 2,6-di-tert-butyl-4-methylphenol, n-octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, and tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane; sulfur-based antioxidants such as dilauryl-3,3'-thiodipropionate and dimyristyl-3,3'-dithiopropionate; and phosphorus-based antioxidants such as trisnonylphenylphosphite and tris(2,4-di-tert-butylphenyl)phosphite. These may be used individually or in combination of two or more.

[0238] The resin composition of the present invention can be prepared by mixing a polyester polyurethane resin (A), an epoxy resin (B), and, if necessary, other components.

[0239] The resin composition of the present invention preferably contains a solvent in that it is preferably used in the state of a solution or dispersion.

[0240] Examples of solvents include alcohols such as methanol, ethanol, isopropyl alcohol, n-propyl alcohol, isobutyl alcohol, n-butyl alcohol, benzyl alcohol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, and diacetone alcohol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, and isophorone; aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and mesitylene; esters such as methyl acetate, ethyl acetate, ethylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; and aliphatic hydrocarbons such as hexane, heptane, cyclohexane, and methylcyclohexane. These solvents may be used individually or in combination of two or more. When the resin composition of the present invention is a solution or dispersion containing a solvent, coating and forming a resin composition layer on a substrate can be performed smoothly, and a resin composition layer of a desired thickness can be easily obtained.

[0241] When the resin composition of the present invention includes a solvent, the solvent is used such that, from the perspective of workability including film-forming ability, the solid content concentration is preferably in the range of 3 mass% to 80 mass%, more preferably 10 mass% to 50 mass%.

[0242] Suitable substrates for the resin composition of the present invention are objects made of polymer materials such as polyimide resin, polyetheretherketone resin, polyphenylene sulfide resin, aramid resin, liquid crystal polymer, etc.; metal materials such as copper, aluminum, stainless steel, etc. The shape of the substrate is not particularly limited. Furthermore, two members made of the same material or different materials as substrates can be bonded together using the resin composition of the present invention to produce an integrated composite. In addition, products having a resin composition layer with adhesive properties, such as the following coverlay film, bonding sheet, etc., can be manufactured.

[0243] (Laminate and laminate with resin composition layer attached)

[0244] The resin composition layer attached laminate of the present invention is a laminate using the resin composition of the present invention, and preferably comprises a resin composition layer formed by the resin composition of the present invention, a resin composition layer in a B-stage state formed by partially curing the resin composition, or a cured layer formed by curing the resin composition, and a substrate film in contact with at least one side of the resin composition layer, the resin composition layer in a B-stage state, or the cured layer.

[0245] In the present invention, the resin composition layer being in a B-stage state refers to a semi-cured state in which a portion of the resin composition layer has begun to cure, and is a state in which the curing of the resin composition layer proceeds further by heating, etc.

[0246] In addition, when using a resin composition containing a solvent, the resin composition layer formed from the resin composition of the present invention is preferably a layer from which at least a portion of the solvent has been removed from the resin composition of the present invention.

[0247] The resin composition layer-attached laminate of the present invention and the laminate of the present invention preferably have a substrate, and more preferably have a layer made of the resin composition of the present invention on the substrate.

[0248] There are no specific restrictions on the description, and publicly available descriptions may be used.

[0249] In addition, as a substrate, it is preferable that it be a film-shaped substrate (substrate film).

[0250] As for the base film, it is preferable that it be a resin film, more preferable that it be a polyimide film or an aramid film, and particularly preferable that it be a polyimide film.

[0251] The above polyimide film or aramid film is not particularly limited as long as it has electrical insulating properties, and may be a film composed solely of polyimide resin or aramid resin, a film containing the resin and additives, etc., and the side on which the resin composition layer is formed may be surface-treated.

[0252] The thickness of the above-mentioned material is not particularly limited, but it is preferably 3 μm to 125 μm.

[0253] In addition, the thickness of the resin composition layer is preferably 5 μm to 50 μm, and more preferably 10 μm to 40 μm.

[0254] As a method for manufacturing a laminate having a resin composition layer attached according to the present invention, for example, a resin composition of the present invention containing a solvent is applied to the surface of a substrate film such as a polyimide film to form a resin composition layer, and then at least a portion of the solvent is removed from the resin composition layer to manufacture a laminate having a resin composition layer in a B-stage state.

[0255] The drying temperature when removing the above solvent is preferably 40°C to 250°C, and more preferably 70°C to 170°C.

[0256] Drying is carried out by passing a laminate coated with a resin composition through a furnace in which hot air drying, far-infrared heating, and high-frequency induction heating are performed.

[0257] The resin composition layer-attached laminate of the present invention may additionally have a release film on the surface of the resin composition layer for storage, etc., if necessary.

[0258] As the above-mentioned release film, known materials such as polyethylene terephthalate film, polyethylene film, polypropylene film, silicone release treatment paper, polyolefin resin coated paper, polymethylpentene (TPX) film, and fluorine resin film are used.

[0259] The thickness of the resin composition layer in the B stage state is preferably 5 μm to 100 μm, more preferably 5 μm to 70 μm, even more preferably 5 μm to 50 μm, and particularly preferably 10 μm to 40 μm.

[0260] The thickness of the above-described film and resin composition layer is selected according to the application, but the substrate film tends to become thinner to improve electrical properties. The preferred thickness of the above-described substrate film is the same as the preferred thickness of the above-described substrate.

[0261] In the resin composition layer-attached laminate of the present invention, the ratio (A / B) of the thickness (A) of the resin composition layer and the thickness (B) of the substrate film is preferably 1 or more and 10 or less, and more preferably 1 or more and 5 or less. In addition, it is preferable that the thickness of the resin composition layer is thicker than the thickness of the substrate film.

[0262] As a method for manufacturing a laminate of the present invention, for example, a resin composition of the present invention containing a solvent is coated on the surface of a substrate film, and then dried in the same manner as in the case of a laminate with a resin composition layer attached to the present invention, and then the surface of the formed resin composition layer is brought into surface contact with a substrate to perform lamination, for example, thermal lamination at 80°C to 150°C. Subsequently, the laminate (substrate film / resin composition layer / substrate) is heat-pressed, and further the resin composition layer is cured by an after-cure to form a cured layer.

[0263] The conditions for heat pressing are not particularly limited as long as pressing is possible, but preferably, they can be performed for 1 minute to 60 minutes at a temperature of 150°C to 200°C and a pressure of 1 MPa to 3 MPa. In addition, the conditions for after-cure are not particularly limited, but preferably, they can be performed for 30 minutes to 4 hours at a temperature of 100°C to 200°C.

[0264] The thickness of the hardened layer is preferably 5 μm to 100 μm, more preferably 5 μm to 70 μm, even more preferably 5 μm to 50 μm, and particularly preferably 10 μm to 40 μm.

[0265] There are no particular limitations on the substrate, and the aforementioned examples may be cited. Among these, a metal substrate may be preferably cited, a copper foil or a plated copper foil may be more preferably cited, and a plated copper foil may be particularly preferably cited.

[0266] In addition, there are no specific restrictions on the shape and size of the substrate, and known ones may be used.

[0267] In addition, one embodiment of the laminate of the present invention may be a flexible copper-clad laminate.

[0268] That is, the flexible copper-clad laminate of the present invention preferably has a cured layer formed by curing a resin composition made of the resin composition of the present invention, and has a polyimide film or an aramid film, a cured layer formed by curing the resin composition of the present invention, and a copper foil laminated thereon.

[0269] In the flexible copper-clad laminate of the present invention, the cured layer and the copper foil may be formed on both sides of a polyimide film or an aramid film. Since the resin composition of the present invention has excellent adhesion to articles containing copper, the flexible copper-clad laminate of the present invention has excellent stability as an integrated product.

[0270] The composition of the above polyimide film or aramid film is the same as that of the polyimide film or aramid film in the coverlay film of the present invention described above.

[0271] The thickness of the hardened layer is preferably 5 μm to 50 μm, and more preferably 10 μm to 40 μm.

[0272] In addition, the copper foil mentioned above is not particularly limited and may use electrolytic copper foil, rolled copper foil, etc.

[0273] In addition, the copper foil may be plated with a known metal or alloy such as gold or silver.

[0274] Examples of one embodiment of the resin composition layer-attached laminate of the present invention include the bonding film, electromagnetic shielding film, coverlay film, etc., described below.

[0275] - Bonding Film -

[0276] The bonding film of the present invention uses the resin composition of the present invention and preferably comprises a resin composition layer in a B-stage state formed by partially curing the resin composition of the present invention, and a release film in contact with at least one side of the resin composition layer.

[0277] In addition, the bonding film of the present invention is also one embodiment of the laminate with attached resin composition layer of the present invention described below.

[0278] In addition, the bonding film of the present invention may be in the form of having a resin composition layer between two release films.

[0279] As the above-mentioned release film, a known one as described above may be used.

[0280] It is preferable that the thickness of the above release film be 20 μm to 100 μm.

[0281] In addition, the thickness of the resin composition layer is preferably 5 μm to 100 μm, and more preferably 10 μm to 60 μm.

[0282] As a method for manufacturing the bonding sheet of the present invention, for example, a method of coating the surface of a release film with a resin composition of the present invention containing a solvent, and then drying it in the same manner as in the case of a laminate with a resin composition layer attached to the present invention described above, may be preferably cited.

[0283] - Electromagnetic shielding film -

[0284] The electromagnetic shielding film of the present invention uses the resin composition of the present invention, and preferably has a resin composition layer formed by the resin composition of the present invention, a resin composition layer in a B-stage state formed by partially curing the resin composition, or a cured layer formed by curing the resin composition.

[0285] In addition, the electromagnetic shielding film of the present invention preferably has the resin composition layer and the protective layer.

[0286] As for the protective layer, any known layer made of an insulating resin composition may be used, and is not particularly limited. Additionally, the protective layer may use a resin component used in the resin composition of the present invention. Furthermore, the protective layer may be formed of two or more layers having different compositions or hardnesses.

[0287] In addition, the protective layer may include, as needed, a curing accelerator, a tackifier, an antioxidant, a pigment, a dye, a plasticizer, a UV absorber, an antifoaming agent, a leveling agent, a filler, a flame retardant, a viscosity modifier, an anti-blocking agent, etc.

[0288] The thickness of the resin composition layer in the electromagnetic shielding film of the present invention is not particularly limited, but is preferably 3 μm to 30 μm from the perspective of conductivity and connectivity with a ground circuit.

[0289] Next, specific embodiments of the method for manufacturing the electromagnetic shielding film of the present invention will be described.

[0290] For example, a method may be used in which a resin composition for a protective layer is coated and dried on one side of a release film to form a protective layer, and a resin composition of the present invention is coated and dried on the protective layer to form a resin composition layer.

[0291] By the manufacturing method described above, an electromagnetic shielding film in a laminated state consisting of a resin composition layer, a protective layer, and a release film can be obtained.

[0292] As a method for providing a resin composition layer and a protective layer, it can be carried out by conventional known coating methods, such as gravure coating, kiss coating, die coating, lip coating, comma coating, blade coating, roll coating, knife coating, spray coating, bar coating, spin coating, dip coating, etc.

[0293] The electromagnetic shielding film of the present invention can be adhered to a printed circuit board, for example, by a heat press. The resin composition layer is softened by heating and flows into the ground portion installed on the printed circuit board by applying pressure. As a result, the ground circuit and the conductive adhesive are electrically connected, thereby enhancing the shielding effect.

[0294] [Example]

[0295] The present invention will be described in detail below based on examples. Furthermore, the present invention is not limited by these examples. Also, in the following description, "parts" and "%" refer to "parts by mass" and "% by mass," respectively, unless otherwise specified.

[0296] Ingredients Used

[0297] 1. Polyester polyurethane resin (A)

[0298] Commercially available and synthetic polyesters were used as the polyesters used in the manufacture of polyester polyurethane.

[0299] <Commercially Available>

[0300] For commercial products, Aaronmelt PES-360HVXM30 and Aaronmelt PES-310S30 manufactured by TOAGOSEI CO., LTD. were used. The number average molecular weight of PES-360HVXM30 was 20,000, and the glass transition point was 65°C. The number average molecular weight of PES-310S30 was 20,000, and the glass transition point was 8°C.

[0301] Synthesis of Polyester Resin (PES-1)

[0302] In a flask equipped with a stirring device, a nitrogen inlet tube, an outlet tube, and a thermometer, 201 parts by mass of dimethyl terephthalate, 86 parts by mass of ethylene glycol, 140 parts by mass of neopentyl glycol, 0.9 parts by mass of trimethylolpropane, and 0.22 parts by mass of zinc acetate as a catalyst were added. The temperature was increased while introducing nitrogen, and methanol was distilled at 150°C to 180°C. Then, 183 parts by mass of isophthalic acid, 0.6 parts by mass of trimethylolpropane, and 0.12 parts by mass of antimony trioxide were added, and water was distilled at 180°C to 210°C. Subsequently, the reaction was continued for 6 hours at 230°C under a reduced pressure of 200 Pa while gradually reducing the pressure. The obtained polyester resin PES-1 had a number average molecular weight of 7,000 and a glass transition point of 60°C. The monomer composition by nuclear magnetic resonance (NMR) analysis was terephthalic acid / isophthalic acid / ethylene glycol / neopentyl glycol = 48 / 52 / 43 / 56 in molar ratio. 180 parts by mass of the synthesized polyester resin were taken, and 378 parts by mass of toluene and 42 parts by mass of methyl isobutyl ketone were added to make a polyester solution.

[0303] <Synthesis of Polyester Polyurethane Resin A1>

[0304] (1) Synthesis of polyester polyurethane resin a1

[0305] 600 parts by mass of PES-360HVXM30, 100 parts by mass of toluene, and 30 parts by mass of 2-butyl-2-ethyl-1,3-propanediol were added to a flask equipped with a stirrer, a reflux dehydration apparatus, and a distillation column. The temperature was raised to 120°C and 100 parts by mass of a solvent containing water was distilled off. Then, the temperature was lowered to 105°C and 0.4 parts by mass of 2,2-bis(hydroxymethyl)propionic acid was added to dissolve the mixture. Afterward, 42 parts by mass of Cosmonate NBDI (NBDI) manufactured by Mitsui Chemicals, Inc. were added, and after 30 minutes, 0.2 parts by mass of dibutyltin dilauric acid were added. After continuing the reaction until a predetermined molecular weight was reached, a solution of polyesterurethane resin a1 was obtained by diluting with toluene / 2-propanol to adjust the solid content concentration to 30%. At that time, the number average molecular weight was 35,000 and the acid value was 2 mgKOH / g.

[0306] <Synthesis of Polyester Polyurethane Resins a2 to a12>

[0307] Regarding the synthesis method of polyester polyurethane resin a1, synthesis was carried out in the same manner as the synthesis method of polyester polyurethane resin a1, except that the polyester, diol, and diisocyanate shown in Table 1 were changed to the mass parts of the table.

[0308] [Table 1]

[0309]

[0310] Abbreviations listed in Table 1 other than those mentioned above are explained below.

[0311] Takenate 600: 1,3-Bis(isocyanatomethyl)cyclohexane, manufactured by Mitsui Chemicals, Inc.

[0312] HDMI: Methylenebis(4-cyclohexyl diisocyanate), manufactured by WANHUA CHEMICAL GROUP CO., LTD., trade name WANNATE (registered trademark) HMDI

[0313] HDI: Hexamethylene diisocyanate, manufactured by Tosoh Corporation, trade name HDI

[0314] Dimerdiol: A carbon-36 diol obtained by reducing a dimer acid, manufactured by Croda Japan KK, product name PRIPOL2033

[0315] 2. Epoxy resin (B)

[0316] The following commercially available product was used.

[0317] (1) Epoxy resin b1

[0318] Bisphenol A novolak-type epoxy resin "EPICLON N-865" manufactured by DIC Corporation (Trade Name)

[0319] (2) Epoxy resin b2

[0320] Bisphenol A type epoxy resin "jER 1055" (product name) manufactured by Mitsubishi Chemical Corporation

[0321] 3. Resin (C) having a carboxyl group or carboxylic acid anhydride structure

[0322] (1) Synthesis of polyamide resin c1

[0323] Polyamide resin c1 was synthesized as follows.

[0324] 65 parts by mass of azelaic acid, 190 parts by mass of dodecane acid, 100 parts by mass of piperazine, and 120 parts by mass of distilled water were added to a flask equipped with a stirrer, a reflux dehydration apparatus, and a distillation column. After raising the temperature to 120°C to evaporate the water, the temperature was raised to 240°C at a rate of 20°C / hour, and the reaction was continued for 3 hours to obtain polyamide resin c1. The amine value of this resin was 4.5 mgKOH / g, and the acid value was 10.5 mgKOH / g.

[0325] (2) Synthesis of polyamide resin c2

[0326] Polyamide resin c2 was synthesized as follows.

[0327] 485 parts by mass of dimer acid, 100 parts by mass of hexamethylenediamine, and 120 parts by mass of distilled water were added to a flask equipped with a stirrer, a reflux dehydration apparatus, and a distillation column. After raising the temperature to 120°C to evaporate the water, the temperature was raised to 240°C at a rate of 20°C / hour, and the reaction was continued for 3 hours to obtain polyamide resin c2. The amine value of this resin was 4.5 mgKOH / g, and the acid value was 10.5 mgKOH / g.

[0328] (3) Synthesis of polyolefin resin c3

[0329] 100 parts by mass of a propylene-butene random copolymer consisting of 80% by mass of propylene units and 20% by mass of butene units, prepared by using a metallocene catalyst as a polymerization catalyst, 1 part by mass of maleic anhydride, 0.3 parts by mass of lauryl methacrylate, and 0.4 parts by mass of di-t-butyl peroxide were mixed using a twin-screw extruder with the maximum cylinder temperature set to 170°C. Subsequently, polyolefin resin c1 was prepared by performing vacuum degassing within the extruder and removing residual unreacted materials. Polyolefin resin c1 had a weight average molecular weight of 80,000 and an acid value of 10 mgKOH / g. In addition, the content ratio of the graft portion in polyolefin resin c1 was 1.5% by mass.

[0330] (4) Synthesis of polyolefin resin c4 (resin that does not have a carboxyl group and carboxylic acid anhydride structure)

[0331] A metallocene catalyst was used as a polymerization catalyst, and 80 mass% of propylene units and 20 mass% of butene units were reacted to obtain polyolefin resin c4. The weight average molecular weight of polyolefin resin c4 was 100,000.

[0332] 4. Imidazolesilane compound (D)

[0333] 1-(2-hydroxy-3-trimethoxysilylpropoxypropyl)imidazole

[0334] 5. Weapon Filler (E)

[0335] (1) Weapon filler e1

[0336] Talc "SG-95" manufactured by NIPPON TALC Co., Ltd. (Product name; average particle size 2.5μm)

[0337] (2) Weapon Filler e2

[0338] Aerosil "R972" (Product name; average particle size 16 nm, silica particles), obtained from Toshin Kasei Co., Ltd.

[0339] 6. Organic filler (F)

[0340] (1) Organic filler f1

[0341] Urethane beads "TK-800T" manufactured by Negami Chemical Industrial Co., Ltd. (Product name; average particle size 8μm)

[0342] (2) Organic filler f2

[0343] Acrylic beads "J-4P" manufactured by Negami Chemical Industrial Co., Ltd. (Product name; average particle size 2.2μm)

[0344] 7. Metal filler (G)

[0345] Copper powder "FCC-115A" manufactured by FUKUDA METAL FOIL & POWDER CO., LTD. (trade name, in terms of particle size distribution, an amount in which particles of 45 μm or less exceed 90 mass%, an amount in which particles of 45 μm to 63 μm are less than 10 mass%, and an amount in which particles of 63 μm to 75 μm are less than 3 mass%)

[0346] 8. Flame retardant

[0347] Clariant manufactured metal phosphinate "Exolit OP935" (trade name)

[0348] 9. Curing accelerator

[0349] Manufactured by SHIKOKU CHEMICALS CORPORATION, imidazole-based curing accelerator "Quazole C11-Z" (trade name)

[0350] 10. Solvent

[0351] A mixed solvent consisting of toluene, methyl isobutyl ketone, and 2-propanol (mass ratio = 100:20:20)

[0352] (Examples 1 to 29, and Comparative Example 1)

[0353] The above-described raw materials were added to a flask equipped with a stirring device in the proportions shown in Table 2 and stirred for 6 hours under heating at 60°C to dissolve component (A), component (B), component (C), an imidazole silane compound, and a curing accelerator in a solvent, and to disperse an inorganic filler, an organic filler, a metal filler, and a flame retardant, thereby preparing a liquid adhesive composition. Subsequently, using all of these liquid adhesive compositions, a coverlay film, a bonding sheet, and adhesive test specimens A and B were prepared, and the evaluations (i) to (ix) below were performed. The evaluation results are shown in Table 2.

[0354] (1) Production of coverlay film

[0355] A liquid adhesive composition was roll-applied to the surface of a 25 μm thick polyimide film so that the thickness after drying was 15 μm, and dried at 120°C for 2 minutes to obtain a coverlay film having an adhesive layer.

[0356] (2) Preparation of adhesive test specimen A

[0357] A rolled copper foil with a thickness of 35 μm manufactured by FUKUDA METAL FOIL & POWDER CO., LTD. was prepared. Then, the mirror surface was overlapped to contact the adhesive layer surface of the coverlay film, and lamination was performed under conditions of 150°C, 0.3 MPa, and 1 m / min. The obtained laminate (polyimide film / adhesive layer / copper foil) was heated and compressed under conditions of 150°C and 3 MPa for 5 minutes, and then further subjected to after-curing in an oven at 160°C for 2 hours to obtain adhesive test specimen A.

[0358] (3) Production of bonding sheets

[0359] A release PET film with a thickness of 35 μm was prepared. Then, a mixture of a liquid adhesive composition and copper powder "FCC-115A" manufactured by FUKUDA METAL FOIL & POWDER CO., LTD. was blended to be 15 mass% of the total solid content of the resin, and the mixture was roll-coated onto the surface of the film to a thickness of 25 μm after drying, and dried at 140°C for 2 minutes to obtain a bonding sheet having an adhesive layer.

[0360] (4) Preparation of adhesive test specimen B

[0361] A flexible printed circuit board was prepared in which a copper circuit pattern was formed on the surface of a nickel-plated SUS304 plate with a thickness of 300 μm and a polyimide film with a thickness of 25 μm, and a coverlay film with a thickness of 37.5 μm having a through hole with a diameter of 1 mm was laminated on the circuit pattern. Initially, the nickel-plated surface of the SUS304 plate was overlapped to contact the adhesive layer surface of the bonding sheet, and lamination was performed under conditions of 150°C, 0.3 MPa, and 1 m / min to obtain a laminate (SUS plate / adhesive layer / release PET film). After that, the release PET film was peeled off, and the surface of the exposed adhesive layer was heat-pressed for 5 minutes at 150°C and 3 MPa on a flexible printed circuit board (a circuit board in which a copper foil circuit is formed on a polyimide with a thickness of 25 μm and a coverlay film with a thickness of 37.5 μm with a diameter of 1 mm is laminated on the copper foil circuit), and then an after-curing was performed in an oven at 160°C for 2 hours to produce an adhesive test specimen B (SUS plate / adhesive layer / flexible printed circuit board).

[0362] (i) Peel-off adhesive strength

[0363] To evaluate adhesion, the 180° peel adhesion strength (N / mm) was measured when the copper foil of each adhesion test specimen A was peeled from the polyimide film under conditions of a temperature of 23°C and a tensile speed of 50 mm / min, in accordance with JIS C 6481 "Test method for copper-clad laminates for printed circuit boards". The width of the adhesion test specimen at the time of measurement was 10 mm. As a result, a peel strength of 0.5 N / mm or more was indicated as "A", a peel strength of 0.35 N / mm or more but less than 0.5 N / mm was indicated as "B", and a peel strength of less than 0.35 N / mm was indicated as "C".

[0364] (ii) Peel adhesion strength after long-term moist heat test

[0365] To evaluate the adhesion after storage at 85°C and 85%RH for 1,000 hours, the 180° peel adhesion strength (N / mm) was measured when peeling the copper foil of each adhesion test specimen A from the polyimide film under conditions of a temperature of 23°C and a tensile speed of 50 mm / min, in accordance with JIS C 6481 "Test method for copper-clad laminates for printed circuit boards". The width of the adhesion test specimen at the time of measurement was 10 mm. As a result, a peel strength reduction rate of less than 15% compared to the initial state was indicated as "A", 15% or more but less than 30% as "B", 30% or more but less than 50% as "C", and 50% or more as "D".

[0366] (iii) Solder heat resistance (appearance during soldering, peel adhesion strength after soldering)

[0367] In accordance with JIS C 6481 (1996), a test was conducted under the following conditions.

[0368] With the polyimide film surface facing upward, the adhesive test specimen A was floated in a solder bath at 260°C for 60 seconds, and the presence or absence of external abnormalities such as expansion or peeling of the adhesive layer was evaluated visually. As a result, "A" was indicated for no external abnormalities such as micro-voids, expansion, or peeling, "B" for slight micro-voids, and "C" for external abnormalities such as expansion or peeling.

[0369] In addition, the 180° peel adhesion strength (N / cm) of the test specimen removed from the above solder bath was measured in accordance with JIS C 6481 when peeling a polyimide film from a plated copper foil at 23°C. The width of the adhesion test specimen at the time of measurement was 10 mm, and the tensile speed was 50 mm / min. As a result, a peel strength reduction rate of less than 15% compared to the initial state was indicated as "A", 15% or more but less than 30% as "B", 30% or more but less than 50% as "C", and 50% or more as "D".

[0370] (iv) Flame retardancy

[0371] The above coverlay film was heat-cured at 160°C for 2 hours, and flame retardancy was evaluated in accordance with UL-94 as defined by Undewriters Laboratories. "A" was used to indicate a passing grade (VTM-0 class), and "F" was used to indicate a failing grade.

[0372] (v) Conductivity (initial, contact resistance)

[0373] The contact resistance value between the SUS plate of the above adhesive test specimen B (SUS plate / adhesive layer / flexible printed circuit board) and the copper foil circuit of the flexible printed circuit board was measured using a resistance meter. As a result, a contact resistance value of less than 0.3Ω was indicated as "A", a contact resistance value of 0.3Ω or more and less than 0.5Ω was indicated as "B", a contact resistance value of 0.5Ω or more and less than 1Ω was indicated as "C", a contact resistance value of 1Ω or more and less than 3Ω was indicated as "D", and a contact resistance value exceeding 3Ω was indicated as "E".

[0374] (vi) Conductivity after soldering (conductivity after soldering, contact resistance)

[0375] The above adhesive test specimen B was floated in a solder bath at 260°C for 60 seconds. Afterward, the contact resistance value between the SUS plate of adhesive test specimen B, which was removed from the solder bath, and the copper foil circuit of the flexible printed circuit board was measured using a resistance meter. As a result, a contact resistance value of less than 0.3Ω was indicated as "A", a contact resistance value of 0.3Ω or more and less than 0.5Ω was indicated as "B", a contact resistance value of 0.5Ω or more and less than 1Ω was indicated as "C", a contact resistance value of 1Ω or more and less than 3Ω was indicated as "D", and a contact resistance value exceeding 3Ω was indicated as "E".

[0376] (vii) Conductivity after long-term reliability testing (conductivity, contact resistance after 1,000 hours of storage at 85℃ and 85%RH)

[0377] The above adhesive test specimen B was left in a constant temperature and humidity bath at 85°C and 85%RH for 1,000 hours. Afterwards, the contact resistance value between the SUS plate of adhesive test specimen B and the copper foil circuit of the flexible printed circuit board was measured using a resistance meter. As a result, a contact resistance value of less than 0.3Ω was indicated as "A", a contact resistance value of 0.3Ω or more and less than 0.5Ω was indicated as "B", a contact resistance value of 0.5Ω or more and less than 1Ω was indicated as "C", a contact resistance value of 1Ω or more and less than 3Ω was indicated as "D", and a contact resistance value exceeding 3Ω was indicated as "E".

[0378] (viii) Conductivity (contact resistance) after cold / hot cycle test

[0379] The adhesive test specimen B was placed in a cold and thermal shock tester at a high temperature (125℃) and a low temperature (-40℃), maintained at -40℃ for 30 minutes, and then maintained at 125℃ for 30 minutes. After performing 1,000 cycles with this cold and thermal cycle as one cycle, the contact resistance value between the SUS plate of adhesive test specimen B and the copper foil circuit of the flexible printed circuit board was measured using a resistance meter. As a result, a contact resistance value of less than 0.3Ω was indicated as "A", a contact resistance value of 0.3Ω or more and less than 0.5Ω was indicated as "B", a contact resistance value of 0.5Ω or more and less than 1Ω was indicated as "C", a contact resistance value of 1Ω or more and less than 3Ω was indicated as "D", and a contact resistance value exceeding 3Ω was indicated as "E".

[0380] (ix) Storage stability of the resin composition

[0381] The adhesive compositions (resin compositions) of Examples 1 to 29 and Comparative Example 1, having the compositions listed in Table 1, were each placed in glass bottles, sealed, and stored at 5°C for a predetermined time to observe the crystallinity of the compositions. After storage for a predetermined time, if gelation or liquid separation of the adhesive compositions was confirmed, it was considered as poor storage stability and an evaluation was performed.

[0382] <Evaluation Criteria>

[0383] A: No gelation or liquid separation was observed for more than one week.

[0384] F: Gelation or liquid separation occurred in less than 1 week.

[0385] [Table 2]

[0386]

[0387] In addition, the unit of the numerical value in each component column of the resin composition listed in Table 2 is parts by mass.

[0388] As is evident from the results shown in Table 2 above, the resin compositions of Examples 1 to 29 were resin compositions in which the cured product obtained compared to the resin composition of Comparative Example 1 had excellent conductivity after long-term storage and after a cold-heat cycle test under a high temperature and high humidity environment.

[0389] In addition, the resin compositions of Examples 1 to 29 had excellent initial peel adhesion strength, peel adhesion strength after soldering, peel adhesion strength after long-term reliability testing, flame retardancy, initial conductivity, and conductivity after soldering.

[0390] The disclosure of Japanese Patent Application No. 2020-178234, filed on October 23, 2020, is incorporated herein by reference in its entirety.

[0391] All documents, patent applications, and technical specifications described in this specification are incorporated by reference in this specification to the same extent as they are specifically described in each document, patent application, and technical specification.

Claims

Claim 1 A resin composition comprising a polyester polyurethane resin (A) and an epoxy resin (B), wherein the diisocyanate component constituting the polyester polyurethane resin (A) comprises a diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms, further comprising an organic filler (F), further comprising a metal filler (G), wherein the metal filler (G) is a conductive filler, and wherein, as an optional component, a resin (C) having a carboxyl group or a carboxylic acid anhydride structure, wherein the content of the metal filler (G) is 10 to 50 parts by mass relative to 100 parts by mass of the total amount of the polyester polyurethane resin (A), the epoxy resin (B), and the optional component resin (C) having a carboxyl group or a carboxylic acid anhydride structure. Claim 2 delete Claim 3 A resin composition according to claim 1, wherein the molecular weight per urethane bond in the polyester polyurethane resin (A) is 200 to 8,000. Claim 4 A resin composition according to claim 1, wherein, with respect to the total amount of the polyester polyurethane resin (A), the epoxy resin (B), the resin having a carboxyl group or carboxylic acid anhydride structure (C), and an imidazole silane compound (D) that may be contained as an optional component, the content of the polyester polyurethane resin (A) is 10 mass% to 90 mass%, and the content of the resin having a carboxyl group or carboxylic acid anhydride structure (C) is 5 mass% to 70 mass%. Claim 5 A resin composition according to claim 1, further containing an inorganic filler (E). Claim 6 delete Claim 7 A resin composition according to claim 1, wherein the diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms has a hydrocarbon structure. Claim 8 A resin composition according to claim 1, wherein the diol component constituting the polyester polyurethane resin (A) comprises a diol compound having a hydrocarbon group having 5 to 32 carbon atoms. Claim 9 A resin composition according to claim 8, wherein the diol compound having a hydrocarbon group having 5 to 32 carbon atoms comprises a diol compound having an alicyclic structure or two or more side chains. Claim 10 A resin composition according to claim 1, wherein the polyester polyurethane resin (A) comprises a polyester polyurethane resin having a polyester structure with a number average molecular weight of 8,000 to 30,000. Claim 11 A resin composition according to claim 1, wherein the number average molecular weight of the polyester polyurethane resin (A) is 10,000 to 80,000. Claim 12 A resin composition according to claim 1, wherein the acid value of the polyester polyurethane resin (A) is 0.1 mgKOH / g to 20 mgKOH / g. Claim 13 A resin composition according to claim 1, wherein the glass transition temperature of the polyester polyurethane resin (A) is 30°C to 150°C. Claim 14 A resin composition according to claim 1, wherein the content of the epoxy resin (B) is 1 to 30 parts by mass with respect to 100 parts by mass of the polyester polyurethane resin (A). Claim 15 In claim 1, the epoxy resin (B) is a resin composition containing bisphenol A type epoxy resin and / or novolak type epoxy resin. Claim 16 A resin composition according to claim 1, wherein the content of the resin (C) having a carboxyl group or carboxylic acid anhydride structure is 1 to 100 parts by mass with respect to 100 parts by mass of the polyester polyurethane resin (A). Claim 17 A resin composition according to claim 1, wherein the resin (C) having a carboxyl group or carboxylic acid anhydride structure comprises at least a portion of a polyamide resin having an acid value and a resin having an acid-modified polyolefin structure. Claim 18 delete Claim 19 delete Claim 20 delete Claim 21 A bonding film comprising a resin composition layer in a B-stage state formed by partially curing a resin composition described in any one of claims 1, 3 to 5, and 7 to 17, and a release film in contact with at least one side of the resin composition layer. Claim 22 A resin composition layer attached laminate comprising a resin composition layer formed by any one of claims 1, 3 to 5, and 7 to 17, a resin composition layer in a B-stage state formed by partially curing the resin composition, or a cured layer formed by curing the resin composition, and a substrate film in contact with at least one side of the resin composition layer, the resin composition layer in the B-stage state, or the cured layer. Claim 23 A laminate having a cured layer formed by curing a resin composition described in any one of claims 1, 3 to 5, and 7 to 17. Claim 24 A flexible copper-clad laminate having a copper foil, a cured layer formed by curing a resin composition described in any one of claims 1, 3 to 5, and 7 to 17, and a substrate. Claim 25 A flexible flat cable comprising copper wiring, a cured layer formed by curing a resin composition described in any one of claims 1, 3 to 5, and 7 to 17, and a sheathing material. Claim 26 An electromagnetic shielding film having a resin composition layer formed by a resin composition described in any one of claims 1, 3 to 5, and 7 to 17, a resin composition layer in a B-stage state formed by partially curing the resin composition, or a cured layer formed by curing the resin composition.

Citation Information

Patent Citations

  • Thermosetting resin composition

    JP2006274258A

  • Conductive adhesive for solar cell, solar cell module, and manufacturing method of solar cell module

    JP2015228457A

  • Thermosetting resin composition and uses thereof

    KR1020080100486A

  • Conductive adhesive, conductive adhesive sheet, wiring device, and method for manufacturing wiring device

    JP2015110769A

  • Novel polyurethane, curable composition, overcoat film, and flexible wiring board and production method therefor

    KR1020180073611A